Focal amplifications are associated with chromothripsis events and diverse prognoses in gastric cardia adenocarcinoma - Zhao, Xue-Ke; Xing, Pengwei; Song, Xin; Zhao, Miao; Zhao, Linxuan; Dang, Yonglong; Lei, Ling-Ling; Xu, Rui-Hua; Han, Wen-Li; Wang, Pan-Pan; Yang, Miao-Miao; Hu, Jing-Feng; et al. (Nature communications, 2021)
The role of focal amplifications and extrachromosomal DNA (ecDNA) is unknown in gastric cardia adenocarcinoma (GCA). Here, we identify frequent focal amplifications and ecDNAs in Chinese GCA patient samples, and find focal amplifications in the GCA cohort are associated with the chromothripsis process and may be induced by accumulated DNA damage due to local dietary habits. We observe diverse correlations between the presence of oncogene focal amplifications and prognosis, where ERBB2 focal amplifications positively correlate with prognosis and EGFR focal amplifications negatively correlate with prognosis. Large-scale ERBB2 immunohistochemistry results from 1668 GCA patients show survival probability of ERBB2 positive patients is lower than that of ERBB2 negative patients when their surviving time is under 2 years, however, the tendency is opposite when their surviving time is longer than 2 years. Our observations indicate that the ERBB2 focal amplifications may represent a good prognostic marker in GCA patients. The role of focal amplifications and extrachromosomal DNA (ecDNA) is unknown in gastric cardia adenocarcinoma (GCA). Here, the authors identify frequent focal amplifications and ecDNAs in Chinese GCA patient samples, as well as the potential associations of these alterations with prognosis and dietary habits.